Parents’ Involvement and Perspectives on Inclusive Education: The case of St. Rita Nursery and Primary school Buea - Atemnkeng , Nkemngong; Aziamin, Norah Asongu (Journal of Research in Innovative Teaching and Inclusive Learning, 2025)
The role of parents in the education and successful implementation of inclusive education globally cannot be undermined. St. Rita is one of the schools holding the flag of inclusion in Buea, Cameroon for over 10 years. This study investigated parents’ involvement and thoughts of inclusive education. Specifically, it investigated how parents get themselves involved in the education of their children, how the school involves parents in terms of decision making with regards to their children and explored parents’ opinions regarding the continued selection of St. Rita as their preferred school for their children. A descriptive survey research design was adopted with a sample size of 36 parents (19 parents of children with disabilities and 16 parents of children without disabilities). An interview guide was the major tool used for data collection. The data was analyzed quantitatively and qualitatively. Data were entered using EpiData version 3.1 and exported to SPSS version 25.0. Quantitative data was analyzed using graphs and percentages while qualitative data were analyzed using thematic analysis approach. Findings from the study showed that, 50% of parents are fully involved in the education of their children while the other 50% are moderately involved. Parents get involved in the education of their children by paying fees, helping them with the assignments at home and visits to school to get information concerning their children. All the parents of children with disabilities confirmed that, the school involves them in decisions about their children. 68.75% parents of children without disabilities affirmed their involvement in decision making concerning their children while 31.25% said they had never been involved. Usual ways the school uses in communicating with the parents involved: messages in writing through their children and school WhatsApp group. Parents stated reasons for continued preference for St. Rita for their children’s education to include inclusive nature of the school, recommendation from others, proximity of the school from their homes and workplaces, teacher efficiency, affordability and previous knowledge of the school. The school is highly recognized by parents of children with disabilities because significant improvement is noticed in their children within a short while after admission into the school.